Implications in Educational, Linguistic, and Psycho-Emotional Development in People with 22q11 Syndrome - Moraleda-Sepúlveda, Esther; López-Resa, Patricia; Santos-Muriel, Noelia; López-Peces, Paula; Frontera, Romina; Pulido-García, Noelia (International Journal of Learning and Development, 2024)
22q11 Syndrome is one of the so-called rare diseases. This syndrome is characterized by certain physical alterations. However, its manifestations also occur in other areas. At the linguistic level, there is mainly an alteration in the production of language. In the educational area, the manifestations of the syndrome cause learning difficulties that will also vary depending on the cognitive level. All these characteristics, of course, have repercussions at the psycho-emotional level, with a greater tendency to the presence of mental disorders. This article aims to highlight which are the most important characteristics of this type of population and propose possible suggestions for intervention in order to minimize these problems. In addition, a series of recommendations are included to improve intervention at all levels and to improve the quality of life of people with 22q11 Syndrome.